Carbon Nanosheets: Nitrogen‐Doped Porous Carbon Nanosheets Templated from g‐C3N4 as Metal‐Free Electrocatalysts for Efficient Oxygen Reduction Reaction (Adv. Mater. 25/2016). Issue 25 (3rd July 2016) - Yu, Huijun; Shang, Lu; Bian, Tong; Shi, Run; Waterhouse, Geoffrey I. N.; Zhao, Yufei; Zhou, Chao; Wu, Li‐Zhu; Tung, Chen‐Ho; Zhang, Tierui
Abstract : T. Zhang and co‐workers report the synthesis of nitrogen‐doped porous carbon nanosheets with extremely high nitrogen content and high surface areas using graphitic carbon nitride (g‐C3 N4 ) as template, nitrogen source, and porogen. As described on page 5080, the nanosheets exhibit outstanding oxygen reduction catalytic activities which are comparable to commercial Pt/C catalysts in alkaline media.